Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2016
DOI: 10.1115/gt2016-57644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gaseous Admixtures on Cycles With Supercritical Carbon Dioxide

Abstract: Supercritical carbon dioxide cycles are recently very perspective and they are researched all around the world. CO2 is an interesting medium for applications in many technologies, from nuclear energy through geothermal, solar and waste heat recovery systems. However, S-CO2 cycles have several issues which have to be researched, one of them being the presence of the so called pinch point in the heat exchangers design. Therefore, the Czech Technical University (CTU) conducts research on supercritical carbon diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The input parameters for the simulation are shown in Table 1. The results obtained were validated with the Thermoflex 27 software [27], UniSim Design R451 software [28] (UniSim uses Peng-Robinson equation of state for thermodynamic property estimations), and scientific articles about the effect of gaseous admixtures on cycles with s-CO2 [1,29,30]. [31,32] ηmc 0.89 -Re-compressor efficiency [31,32] ηrc 0.89 -Turbine efficiency [31,32] ηt 0.93 -Heat exchanger conductance for low temperature recuperator UALT 2500 // 5000 // 7500 kW/K Heat exchanger conductance for high temperature recuperator UAHT 2500 // 5000 // 7500 kW/K Split fraction γ Optimized - 1 CIT optimized for group A mixtures.…”
Section: Assumptions and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The input parameters for the simulation are shown in Table 1. The results obtained were validated with the Thermoflex 27 software [27], UniSim Design R451 software [28] (UniSim uses Peng-Robinson equation of state for thermodynamic property estimations), and scientific articles about the effect of gaseous admixtures on cycles with s-CO2 [1,29,30]. [31,32] ηmc 0.89 -Re-compressor efficiency [31,32] ηrc 0.89 -Turbine efficiency [31,32] ηt 0.93 -Heat exchanger conductance for low temperature recuperator UALT 2500 // 5000 // 7500 kW/K Heat exchanger conductance for high temperature recuperator UAHT 2500 // 5000 // 7500 kW/K Split fraction γ Optimized - 1 CIT optimized for group A mixtures.…”
Section: Assumptions and Methodsmentioning
confidence: 99%
“…The input parameters for the simulation are shown in Table 1. The results obtained were validated with the Thermoflex 27 software [27], UniSim Design R451 software [28] (UniSim uses Peng-Robinson equation of state for thermodynamic property estimations), and scientific articles about the effect of gaseous admixtures on cycles with s-CO 2 [1,29,30].…”
Section: Assumptions and Methodsmentioning
confidence: 99%
“…On the other hand, in engineering application of Brayton cycle, S-CO 2 will be inevitably mixed with the gas impurities. Therefore, Vesely et al [24] investigated the effect of gaseous admixtures on the cycle efficiency at a fixed inlet temperature of main compressor. They found that all researched mixtures except CO 2 -H 2 S had negative effects on the cycle efficiency and net power output.…”
Section: Current Status Of Co 2 -Based Mixturesmentioning
confidence: 99%
“…However, due to the fact that T c is different for various mixtures, this assumption will cause the performance comparison of mixtures under different compressor inlet temperatures. (2) For the work of Vesely et al [24,25] and Guo et al [23], the range of employed gas fraction is too less. Although Baik and Lee [22] considered the whole fraction range 0-1, most of the employed additives belong to organic fluids, which may decompose in the high temperature.…”
Section: Current Status Of Co 2 -Based Mixturesmentioning
confidence: 99%
See 1 more Smart Citation